Lactate: The Mediator of Metabolism and Immunosuppression - Zhang, Yuanyuan; Zhai, Zhao; Duan, Jiali; Wang, Xiangcai; Zhong, Jinghua; Wu, Longqiu; Li, An; Cao, Miao; Wu, Yanyang; Shi, Huaqiu; Zhong, Jianing; Guo, Zhenli (Frontiers in Endocrinology, 2022)
The Warburg Effect, one of the hallmarks of tumors, produces large amounts of lactate and generates an acidic tumor microenvironment via using glucose for glycolysis. As a metabolite, lactate not only serves as a substrate to provide energy for supporting cell growth and development, but also acts as an important signal molecule to affect the biochemical functions of intracellular proteins and regulate the biological functions of different kind of cells. Notably, histone lysine lactylation (Kla) is identified as a novel post modification and carcinogenic signal, which provides the promising and potential therapeutic targets for tumors. Therefore, the metabolism and functional mechanism of lactate are becoming the one of hot fields in tumor research. Here, we review the production of lactate and its regulation on immunosuppressive cells, as well as the important role of Kla in hepatocellular carcinoma. Lactate and Kla supplement the knowledge gap in oncology and pave the way for exploring the mechanism of oncogenesis and therapeutic targets. There is a lot of research space in the future.